2010
DOI: 10.1089/acm.2009.0213
|View full text |Cite
|
Sign up to set email alerts
|

Using Traditional Spirituality to Reduce Domestic Violence Within Aboriginal Communities

Abstract: Including elders in the care of people who are the recipients of domestic violence is effective. We speculate that it helps by providing traditional stories about relationships and roles that do not include violence. Spiritual approaches within aboriginal communities may be more effective than more secular, clinical approaches. Research is indicated to compare elder-based interventions with conventional clinical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 24 publications
3
48
1
2
Order By: Relevance
“…40 Access to Elders as part of routine primary care offers one important avenue for meaningful participation in cultural practices that can improve Indigenous patients' care and help reduce inequities. Our findings are consistent with research showing that the inclusion of Elders in health care initiatives led to a reduction in teen suicides, 23 decreased rates of domestic violence, 24 improved quality of life, reduced depressive and trauma symptoms, 41 and improved understanding and trust between Indigenous and non-Indigenous staff and patients. 25 Our research suggests that working with Elders allowed some participants to "open up" and become more receptive to engaging with other health care providers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…40 Access to Elders as part of routine primary care offers one important avenue for meaningful participation in cultural practices that can improve Indigenous patients' care and help reduce inequities. Our findings are consistent with research showing that the inclusion of Elders in health care initiatives led to a reduction in teen suicides, 23 decreased rates of domestic violence, 24 improved quality of life, reduced depressive and trauma symptoms, 41 and improved understanding and trust between Indigenous and non-Indigenous staff and patients. 25 Our research suggests that working with Elders allowed some participants to "open up" and become more receptive to engaging with other health care providers.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research found that involving Elders in a community mental health promotion strategy for teens resulted in a reduction in suicides. 23 Involving Elders in patient care has also been shown to substantially decrease rates of domestic violence, 24 and to improve understanding and trust between Indigenous and non-Indigenous staff and patients. 25 Our study is part of a larger investigation examining the impact of an Indigenous Elders program on the mental health and well-being of Indigenous patients in an inner city primary care setting.…”
mentioning
confidence: 99%
“…Connecting Native patients with their Native culture promotes better health outcomes. 14,35 Our findings are based on interviews we completed with six Native healers and are not intended to represent or speak for all Native people, who represent a diversity of cultures, lan-ORIGINAL RESEARCH & CONTRIBUTIONS "Our Culture Is Medicine": Perspectives of Native Healers on Posttrauma Recovery Among American Indian and Alaska Native Patients guages, and beliefs. Our aim in this project was to inform the development of a care-management intervention with Native trauma patients to be implemented at a level 1 trauma center.…”
Section: Discussionmentioning
confidence: 99%
“…10 For example, aboriginal families receiving clinical care for domestic violence that integrated treatment by traditional healing elders showed significant improvement compared with families who did not participate in the integrated treatment. 14 Since the 1990s, indigenous scholars working in mental health among Native communities have called for traditional healing practices to inform (and even transform) conventional psychotherapy. [14][15][16][17] Mohatt emphasized the need for a practical grounding of indigenous psychotherapy theories in the reality of clinical practice, suggesting that case studies be used as a way to test theory in practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation